Packaging in the greening of the supply chain - Jankowski, Łukasz; Cwajda, Rafał; Gradek, Łukasz; Goszczyńska, Anna Dorota (Contemporary challenges of transport, freight forwarding and logistics - selected aspects, 2023)
Packaging is essential for the transport of goods. In the context of the transformation of the current economy towards a green economy, researchers of the subject pay attention to the issue of the materials from which packaging is made, whether it can be recycled (including to what extent), or whether it can be reused in the transport process. Hence, the impact of packaging on the environment and the greening of the supply chain through the implementation of appropriate packaging (including eco-friendly packaging) are increasingly being addressed in various scientific studies. These aspects have become an area of scientific consideration in this chapter. Based on a bibliometric analysis using the VOSviewer software, the key areas around which packaging in the context of a green supply chain is addressed in research are presented. The chapter also presents implemented solutions aimed at greening the supply chain around packaging in selected business entities.